2017
DOI: 10.1002/etc.4020
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a biotic ligand model for predicting the chronic toxicity of dissolved and precipitated aluminum to aquatic organisms

Abstract: Aluminum (Al) toxicity to aquatic organisms is strongly affected by water chemistry. Toxicity-modifying factors such as pH, dissolved organic carbon (DOC), hardness, and temperature have a large impact on the bioavailability and toxicity of Al to aquatic organisms. The importance of water chemistry on the bioavailability and toxicity of Al suggests that interactions between Al and chemical constituents in exposures to aquatic organisms can affect the form and reactivity of Al, thereby altering the extent to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 25 publications
1
56
0
Order By: Relevance
“…It is possible that hardness may affect membrane permeability because Ca 2þ ions are known to have this effect in fish [5,7], which may also protect against negative respiratory effects of Al hydroxides. The DOC and pH likely influence toxicity owing to controls over the formation of colloidal Al precipitates or via direct control over Al bioavailability [16]. The DOC effects evaluated in the present study were based on laboratory exposures to Suwannee River NOM, which is a commonly used natural form of DOC for metal toxicity studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that hardness may affect membrane permeability because Ca 2þ ions are known to have this effect in fish [5,7], which may also protect against negative respiratory effects of Al hydroxides. The DOC and pH likely influence toxicity owing to controls over the formation of colloidal Al precipitates or via direct control over Al bioavailability [16]. The DOC effects evaluated in the present study were based on laboratory exposures to Suwannee River NOM, which is a commonly used natural form of DOC for metal toxicity studies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these tests were used in the development of an Al biotic ligand model (BLM), which, based on the water quality parameters that drive Al speciation, can predict the toxicity of both dissolved and precipitated forms of Al to aquatic organisms [16]. Unlike BLMs for other metals (e.g., copper and zinc [4,36]), which are based exclusively on dissolved metal concentrations and chemical speciation, the BLM for Al incorporates the effects of both dissolved and precipitated forms of Al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not an early-life stage test as defined in USEPA guidelines [12], but testing demonstrated that this test had a comparable sensitivity to Al as an early-life stage test (Supplemental Data, Table S1). All Al toxicity data used in the present evaluation are expressed as total Al because this includes both dissolved and precipitated forms of Al that contribute to potential toxicity in laboratory waters [9,11,13].…”
Section: Data Sourcesmentioning
confidence: 99%